PENGEMBANGAN FASILITAS DI KONSERVASI GAJAH TAMAN HUTAN RAYA SULTAN SYARIF HASYIM KABUPATEN SIAK - Alanda, Tengku Said Almer; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The reseacrh aims to find out how the development of facilities in Elephant Conservation Sultan Syarif Hasyim Forest Park Siak District.This study used a descriptive quantitative method to examine problems in the lift. The samples in this study were 50 respondents, who were taken by using simpel random sampling. While data collection techniques in this study using observation, questioner, and literature. By using a Likert scale as a measure to determine the length of the short interval. From the results of research that’s been done, it looks that development of facilities in Elephant Conservation Sultan SyarifHasyim Forest Park Siak District is good enough.Keywords: Development, Facilities.